Exploring Maladaptive Coping in Young Children Using Smartphones: A Qualitative Study - Muthmainah; Kurniasari, Mitta (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Smartphones for children have shown both positive and negative impacts on their development. The study aimed to analyze smartphone content that affected children’s maladaptive coping and the form of maladaptive coping. The study approach was qualitative phenomenology. The study’s informants consisted of 30 parents, five teachers, and 30 children aged 4–6 years at an early childhood education (ECE) institution. Data were collected through in-depth interviews and observations. Based on the results of data analysis, it was known: 1) Smartphone content that causes maladaptive coping, namely in the form of overstimulating content, violent games, anger/tantrum videos, fear-inducing content, and addictive content, has an impact. 2) The characteristics of maladaptive coping behavior in children triggered by digital content. Screen time, educational approaches, and learning emotional regulation from adults were the main keys to shaping adaptive coping strategies in children.